Changing Attitudes of Commercial Airline Pilots Towards Organizations after the COVID-19 Pandemic - Tuathong, Nuttee (KBU Journal of Aviation Management:KBUJAM, 2024)
This study investigates the effects of the changing attitudes and behaviors of commercial airline pilots toward organizations after the COVID-19 pandemic on corporate culture. It examines the factors influencing these attitudes and behaviors, as well as the challenges associated with returning to normalcy in aviation industry post-pandemic. The research is grounded in literature review of 10 key articles related to the commercial airline pilot profession and its impact on organizational culture. The aviation and tourism sectors were among the first to be severely impacted by the COVID-19 pandemic, with airlines worldwide, including those in Thailand – such as Thai Airways, AirAsia, Nok Air, Lion Air and Bangkok Airways – facing unprecedented challenges. In an effort to survive the crisis, these airlines implemented drastic measures, including laying off numerous pilots and personnel and reducing pilot compensation. These actions not only disrupted the operational stability of the airlines but also had significant repercussions on the mental health of pilots, who had previously been well-compensated and regarded as having a stable and prestigious vacation.